Improving Speaking Communication Skills in English through Self-Directed Strategy - Cejay Lou Alaon; Jesly Delos Santos; Ariel San Jose (Universitas Majalengka, 2023)
The purpose of this study was to explore the importance of Self-Directed Learning technique in improving the communication skills in English of students. Sixteen sophomore BS Education majors in English were chosen on purpose. Focus groups were conducted to obtain the necessary information. The analysis of information yielded five themes: increasing language competency, encouraging independent learning, learning through the internet, and becoming more reading focused. Each theme were discussed. It was concluded that regardless of the good implications that Self-Directed Learning brings to learners, the truth remains that students who use Self-Directed Learning requires the guidance and monitoring of teachers in order for students to completely appreciate the significant effects and benefits of the technique. Giving students complete control over their learning can lead to inaccuracy and danger. The results implicate the current situation of COVID 19 where academic institutions are adapting the blended and flexible modalities.